2009
DOI: 10.1088/0004-637x/704/2/891
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Magnetic Field in Turbulent Molecular Clouds

Abstract: One of the key problems in star formation research is to determine the role of magnetic fields. Starting from the atomic inter-cloud medium (ICM) which has density n H ~ 1 cm −3 , gas must accumulate from a volume several hundred pc across in order to form a typical molecular cloud. Star formation usually occurs in cloud cores, which have linear sizes below 1 pc and densities n H2 > 10 5 cm −3 . With current technologies, it is hard to probe magnetic fields at scales lying between the accumulation length and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
118
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 36 publications
19
118
1
Order By: Relevance
“…The magnetic fields seem to have a bimodal behavior, where the field is either parallel or perpendicular to the major axis of the cloud (Li et al 2009(Li et al , 2013Soler et al 2013;Planck Collaboration et al 2016a. This orderliness and bimodality of the magnetic fields is also observed at the 0.1-0.01 pc protostellar core scale (Koch et al 2014;Zhang et al 2014).…”
Section: Magnetic Fields At Different Spatial Scalesmentioning
confidence: 97%
“…The magnetic fields seem to have a bimodal behavior, where the field is either parallel or perpendicular to the major axis of the cloud (Li et al 2009(Li et al , 2013Soler et al 2013;Planck Collaboration et al 2016a. This orderliness and bimodality of the magnetic fields is also observed at the 0.1-0.01 pc protostellar core scale (Koch et al 2014;Zhang et al 2014).…”
Section: Magnetic Fields At Different Spatial Scalesmentioning
confidence: 97%
“…Li et al (2009) used optical backgroundstarlight polarimetry to probe field morphology on cloud scales (200 pc) and sub-millimeter dust polarimetry to probe fields on much smaller core scales (a few × 0.1 pc). They showed that magnetic-field orientations are broadly consistent from cloud-to core-scales.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 2009). However, as of today, no consistent scenario exists that explains how magnetic fields in Herbig Ae/Be stars are generated and how they interact with the circumstellar environment.…”
Section: Introductionmentioning
confidence: 99%